Development of Social Studies Learning Outcomes with Tajhin Peddhis-Based Etnopedagogy Approach - Emi Tipuk Lestari; Saiful Bahri (AL-ISHLAH: Jurnal Pendidikan, 2021)
The purpose of this study was to describe social studies learning outcomes with an Ethno pedagogy approach based on the tajhin pheddis tradition. The research method is classroom action research with the Spiral Model from Kemmis and Taggart. In general, four stages are usually passed, namely: Planning, Acting, Observing, and Reflecting. The subjects or informants are social studies teachers and Class VII students at Madrasah Tsanawiyah. This study's techniques and data collection tools were observation and interview techniques. Student learning outcomes have increased between cycle 1 and cycle 2. The increase in learning outcomes can be seen from the average cycle 1 of 62, 5. The average value in cycle II has increased by 79, 5, while the average presentation of completeness in the cycle This II increased to 80% of students who completed above the KKM score. Based on the average value and the percentage of classical learning completeness, it can be concluded that social studies learning with an ethnopedagogic approach based on the tajhin pheddis tradition can improve student learning outcomes in social studies subjects. Learning with an ethnopedagogic approach through the tajhin tradition pheddis can be an approach in social studies learning that is meaningful learning. It is shown that the study results indicate an increase in student learning outcomes at MTs AL-Ikhlas Kuala Mandor B.